2016
DOI: 10.1186/s13069-016-0044-2
|View full text |Cite
|
Sign up to set email alerts
|

Protective role for miR-9-5p in the fibrogenic transformation of human dermal fibroblasts

Abstract: BackgroundExcessive accumulation of extracellular matrix (ECM) proteins is the hallmark of fibrotic diseases, including skin fibrosis. This response relies on the activation of dermal fibroblasts that evolve into a pro-fibrogenic phenotype. One of the major players in this process is the cytokine transforming growth factor-β (TGF-β). MicroRNAs (miRNAs) are small non-coding RNAs that post-transcriptionally regulate gene expression affecting a wide range of pathophysiological events including fibrogenesis. Micro… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
31
0

Year Published

2017
2017
2022
2022

Publication Types

Select...
5
3

Relationship

2
6

Authors

Journals

citations
Cited by 23 publications
(31 citation statements)
references
References 68 publications
0
31
0
Order By: Relevance
“…On the contrary, this effect was not observed in the PGC-1α −/− mice. 33 In previous work, 34,35 we identified miR-9-5p as a miRNA with anti-fibrotic potential in the lung, peritoneum, and skin. In these experiments the expression of miR-9-5p was not different between wild type and knockout (KO) mice in both the healthy (contralateral) or obstructed kidneys (UUO) (data not shown).…”
Section: The Protective Role Of Mir-9-5p In Kidney Fibrosis Is Medimentioning
confidence: 96%
See 1 more Smart Citation
“…On the contrary, this effect was not observed in the PGC-1α −/− mice. 33 In previous work, 34,35 we identified miR-9-5p as a miRNA with anti-fibrotic potential in the lung, peritoneum, and skin. In these experiments the expression of miR-9-5p was not different between wild type and knockout (KO) mice in both the healthy (contralateral) or obstructed kidneys (UUO) (data not shown).…”
Section: The Protective Role Of Mir-9-5p In Kidney Fibrosis Is Medimentioning
confidence: 96%
“…Its expression is increased in both patient samples and animal models of CKD and acute kidney injury (AKI). 34,35 We hypothesized that miR-9-5p could also be beneficial in renal fibrosis. 23,32 Nevertheless, there are few reports identifying miRNAs with a protective action as ongoing therapeutic efforts are based on attempts to antagonize a specific miRNA, which given its multiplicity of targets may result in unwanted side effects.…”
Section: Introductionmentioning
confidence: 99%
“…During the current study, the targeting relationship between microRNA‐296‐3p (miR‐296‐3p) and downstream of tyrosine kinase (DOK) 2 was determined through the application of an initial bioinformatics prediction followed by a confirmatory dual luciferase reporter assay. As an important subgroup of short noncoding RNAs, microRNAs (miRs) play essential roles in a large array of physiologic and pathologic conditions in which their aberrant expression has been correlated with disease pathogenesis and progression, including fibrogenesis (14, 15). As previously reported by Wang et al .…”
mentioning
confidence: 99%
“…During the current study, the targeting relationship between microRNA-296-3p (miR-296-3p) and downstream of tyrosine kinase (DOK) 2 was determined through the application of an initial bioinformatics prediction followed by a confirmatory dual luciferase reporter assay. As an important subgroup of short noncoding RNAs, micro-RNAs (miRs) play essential roles in a large array of physiologic and pathologic conditions in which their aberrant expression has been correlated with disease pathogenesis and progression, including fibrogenesis (14,15). As previously reported by Wang et al (16), the low expression of miR-296 has been earmarked as a responsible element associated with unfavorable survival rates and poor prognoses among patients with hepatocellular carcinoma, whereas up-regulated expression levels of miR-296 exhibit tumor suppressor capabilities.…”
mentioning
confidence: 99%
“…For instance, miR-9-5p regulates cardiac fibrosis by targeting PDGFR-β in rats [26]. A recent study has demonstrated that miR-9-5p has a protective role in the fibrogenic transformation of human dermal fibroblasts [27]. In liver fibrosis, a recent study shows that miR-9-5p not only inhibits HSC proliferation and activation in vitro but also inhibited CCl 4 -induced liver fibrosis in mice [11].…”
Section: Discussionmentioning
confidence: 99%